Spatial changes to climatic suitability and availability of agropastoral farming systems across Kenya (1980–2020) - Lawrence, T.J.; Vilbig, J.M.; Kangogo, G.; Fèvre, Eric M.; Deem, S.L.; Gluecks, Ilona V.; Sagan, V.; Shacham, E. (SAGE Publications, 2023)
Productive global agriculture is under a convergence of pressures, and particularly climate change and population growth. The impact is especially stark in East Africa where crop production is mostly rain-fed and population growth rates are among the highest in the world. Our objective for this study was to understand how climate change and population growth have impacted the size of agropastoral areas across Kenya over 40 years. Climate-suitable areas for all primary crops decreased 28% over the study period. Climate-suitable areas for primary crops increased 3% in highly productive counties, decreased 25% in moderately productive counties, and decreased 62% in low productive counties. Climate-suitable areas over the study period decreased 13% for ranching areas, 21% for dairying areas, 24% for mixed crop and ranching areas, and 28% for mixed crop and dairying areas, while climate-suitable areas for pastoralism increased 12%. Population across Kenya more than tripled over the study period, while population relative to climate-suitable areas for crops increased nearly fourfold, and population relative to climate-suitable areas for pastoralism nearly tripled. Population relative to available climate-suitable areas for crops more than doubled in highly productive counties, increased more than four-fold in moderately productive counties, and was nearly 15 times higher in low productive counties. Examining the cumulative effects of climate change and population growth on agricultural sectors across Kenya can help to develop policies and strategies to reach the UN Sustainable Development Goals.